ANALISIS PAJAK PENGHASILAN PASAL 23 ATAS JASA SEWA ALAT BERAT PADA PT. SUMATRA UNGGUL PALEMBANG - Reni Hardianti; Koefrowi . (Universitas Tridinanti, 2020)
ABSTRACK The purpose of this study is to determine the income tax on heavy equipment rental services at PT. Sumatra Excellent. The data used in writing in this study is secondary data in the form of a list of financial statements whose data sources come from PT. Sumatra Excellent Palembang. The sample used is the 2019 rental service income report. While the analysis techniques are quantitative analysis techniques and qualitative analysis techniques. The results obtained show that PPh Article 23 on heavy equipment rental services related to the calculation, deposit and reporting of the imposition of PPh article 23 PT. Sumatra Unggul which occurred in March, April, June, August, October and November have been in accordance with applicable regulations. However, the calculation of Income Tax Article 23 in January, February, May, July, September and December is not in accordance with Law Number 36 of 2008.Keywords : Income Tax Article 23, Calculation, Deposit, Reporting